Efficiency of regulatory procedures for cage culture aquaculture in the state of São Paulo: Contributions to public policies (Research, Society and Development, 2024)
The regulation of aquaculture is essential for the legality and sustainability of the activity. This study aimed to evaluate the effectiveness of aquaculture regulations and identify gaps in the process. The assessment was conducted through a narrative review of the literature to evaluate the efficiency of regulatory procedures, while gaps were identified by examining standards and procedures on official websites and through consultations with producers and technicians. The regulations and steps for legalization were compiled, covering federal (Concession of Use, General Fishing Activity Registry, Aquaculture License, Federal Technical Registry) and state levels (Environmental Licensing, Authorization for Intervention in PPA, Aquaculture Activity Compliance Declaration - DCAAq). Flowcharts were developed to illustrate the steps and agencies involved. Despite online improvements, challenges persist, such as a lack of information and standardization, delays, and low approval rates. The DCAAq, although efficient, does not cover all the necessary steps.